PENGEMBANGAN KAWASAN WISATA BOROBUDUR HIGHLAND DENGAN KONSEP NOMADIC TOURISM (OBJEK STUDI: ZONA OTORITA KAWASAN PARIWISATA BOROBUDUR, KABUPATEN PURWOREJO, JAWA TENGAH) - Gabriela Bunga Permata Sari; Parino Rahardjo; Sylvie Wirawati (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2019)
The government issued 10 Priority Tourism Destinations consisting of 7 KSPN (National Tourism Strategic Areas) and 3 KEK (Special Economic Zones), one of which was Borobudur. The Borobudur Highland Tourism Area was developed with the concept of Nomadic Tourism determined by the Ministry of Tourism. However, there is no planning and development for this tourist area. With qualitative and quantitative methods, 8 analyzes were carried out, namely analysis of carrying capacity of the environment, location analysis, site analysis, analysis of nomadic tourism components, analysis of best practices, market analysis, plan analysis, development and investment analysis. The purpose and objective of this study is to develop a plan for the development and potential of products that will be developed in the Borobudur Highland Tourism Area with the concept of nomadic tourism. The results to be issued are development plans in the form of a master plan. AbstrakPemerintah mengeluarkan 10 Destinasi Pariwisata Prioritas yang terdiri dari 7 KSPN (Kawasan Strategis Pariwisata Nasional) dan 3 KEK (Kawasan Ekonomi Khusus), salah satunya adalah Borobudur. Kawasan Wisata Borobudur Highland dikembangkan dengan konsep Nomadic Tourism yang ditentukan oleh Kementrian Pariwisata. Namun, belum ada perencaaan dan pengembangan untuk kawasan wisata ini. Dengan metode kualitatif dan kuantitatif dilakukan 8 analisis yaitu analisis daya dukung lingkungan, analisis lokasi, analisis tapak, analisis komponen nomadic tourism, analisis best practices, analisis pasar, analisis rencana pengembangan dan analisis investasi. Tujuan dari penelitian ini adalah menyusun rencana pengembangan dan potensi produk yang dikembangkan di Kawasan Wisata Borobudur Highland dengan konsep nomadic tourism. Hasilnya yaitu rencana pengembangan dalam bentuk masterplan.